GERMINAL CENTER B CELL DYNAMICS - Mesin, Luka (Immunity, 2016)
Germinal centers (GCs) are the site of antibody diversification and affinity maturation, and as such are vitally important for humoral immunity. The study of GC biology has undergone a renaissance in the past 10 years, with a succession of findings that have transformed our understanding of the cellular dynamics of affinity maturation. In this review, we discuss recent developments in the field, with special emphasis on how GC cellular and clonal dynamics shape antibody affinity and diversity during the immune response.